Navigating the Linguistic Labyrinth: Unraveling the Complexities of Translating the Qur'an into the Banjar Language - Saifuddin; Dzikri Nirwana; Norhidayat; Mowafq Abrahem Masuwd (RaSAIL Media Group, Semarang, Indonesia, 2024)
This research focuses on the challenges in translating the Quran into Banjar. This paper aims to explore the unique challenges that arise during the process of translating the Qur'an from Arabic into the Banjar language. Translating the Qur'an transforms texts from the source language into the target language, which is often faced with various complex problems. These problems are related to the miracles of the Qur'an, the distinct characteristics of the source language (Arabic) and the target language (Banjarese), and things related to the problem of diction, idioms, pronoun usage, grammatical rules, and spelling rules. The research method used is a qualitative approach with content analysis. Data were obtained from literature studies related to translation theory, linguistics, and Qur'an studies. The results of the study show that there are several main challenges in translating the Qur'an into Banjar, including (1) differences in the structure and grammatical system between Arabic and Banjar, (2) difficulties in expressing theological and metaphysical concepts of the Qur'an in Banjar, (3) there is a cultural gap between Arabic traditions and Banjar culture, and (4) the limitation of vocabulary in Banjar to translate specific terms in the Quran. This research enriches our understanding of the challenges in translating religious sacred texts, especially the Quran, into local languages. The findings of this study can be a reference for Qur'an translators and other stakeholders to promote a broader and more inclusive understanding of the Qur'an in Indonesia.